KARAKTERISASI DAN IDENTIFIKASI MOLEKULER BAKTERI ASAM LAKTAT ASAL IKAN RINUAK (PSILOPSIS SP) SEBAGAI KANDIDAT PROBIOTIK HALAL DARI DANAU MANINJAU SUMATERA BARAT - Annita Annita; Eliza Zahra; Heppy Setya Prima (Jurnal Kesehatan Medika Saintika, 2025)
Lactic Acid Bacteria (LAB) have recently become one of the main topics of discussion in the fields of health, food industry, science, animal husbandry, agriculture. LAB plays an important role in efforts to reduce stunting through various mechanisms related to intestinal health and nutrient absorption. One source of LAB is fermented Rinuak fish (Psilopsis sp) from Lake Maninjau, West Sumatra, Indonesia, which is isolated from probiotic bacteria which have the potential to act as antimicrobials, but must be ensured that they are halal in accordance with Islamic religious teachings. The aim of this study was to examine the antimicrobial potential of probiotic LAB isolated from Rinuak fish (Psilopsis sp). The research methods carried out were as follows: isolation and characterization of Rinuak fish (Psilopsis sp) LAB DNA, followed by assessment of the antimicrobial activity of the raw bacteriocin supernatant. Then, 16S rRNA was used to assess LAB isolate species that potentially had antimicrobial activity. The results showed that 3 samples of Rinuak fish (Psilopsis sp), After testing its ability to kill pathogenic bacteria, it was found that IR1 isolate had the greatest antimicrobial activity against Escherichia coli ATCC 0157 (30..27 mm), Staphylococcus aureus ATCC 25923 (25.65 mm) and Listeria monocytogenes CFSAN 004330 (18.65 mm) while the diameter of the inhibition zone by the supernatant of lactic acid bacteria Crude bacteriocin against Escherichia coli ATCC 0157 was 18.87 mm, Staphylococcus aureus ATCC 25923 was 22.67 mm while Listeria monocytogenes CFSAN 004330 did not form an inhibition zone. The results of molecular identification using 16S rRNA showed that the isolated lactic acid bacteria were 99.64% similar to those isolated from Rinuak fish (Psilopsis sp) with Lentilactobacillus buchneri subsp. silagei CD034 strain 17-16, which has antimicrobial potential against pathogenic bacteria. Lentilactobacillus buchneri subsp. silagei CD034 strain 17-16 can be used as an antidiarrheal and antityphoid drug in humans as well as a natural preservative in food that is guaranteed halal